2018
DOI: 10.1155/2018/3865434
|View full text |Cite
|
Sign up to set email alerts
|

Single Oral Acute Toxicity of Banhasasim‐Tang and Its Antiobesity Effect on Diet‐Induced Obese Mice and 3T3‐L1 Adipocytes

Abstract: We had tested antiobesity effect of 52 traditional herbal formulas in 3T3-L1 adipocyte, and Banhasasim-tang (BHSST) was chosen as one of the effective medications to inhibit triglyceride accumulation. We investigated the antiobesity effect of BHSST on 3T3-L1 adipocytes and high-fat diet- (HFD-) induced obese mice. In addition, we evaluated the acute toxicity of BHSST in Sprague Dawley (SD) rats. Differentiated 3T3-L1 cells were treated with various concentrations of BHSST for 8 days. Accumulated triglyceride l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…BHS is currently prescribed for the treatment of upper abdomen swelling and the resulting hiccups, nausea, vomiting, and diarrhea. A recent study demonstrated that BHS shows an anti-obesity effect in high fat diet induced obese mice and 3T3-L1 adipocytes [12]. Another previous study revealed that BHS has an anti-apoptotic effect on chronic acid reflux esophagitis [13].…”
Section: Introductionmentioning
confidence: 98%
“…BHS is currently prescribed for the treatment of upper abdomen swelling and the resulting hiccups, nausea, vomiting, and diarrhea. A recent study demonstrated that BHS shows an anti-obesity effect in high fat diet induced obese mice and 3T3-L1 adipocytes [12]. Another previous study revealed that BHS has an anti-apoptotic effect on chronic acid reflux esophagitis [13].…”
Section: Introductionmentioning
confidence: 98%